Respon Produksi Susu atas Penggunaan Input pada Usahaternak Sapi Perah (Survei di Wilayah Kerja KPBS Pangalengan) - Ardiansyah, Rudeni; Hadiana, Muhammad Hasan; Firmansyah, Cecep (Universitas Galuh, 2024)
The production function or response function is quantitatively described by a regression equation which explains the relationship between production results as a response variable and several inputs used in that production. The level coefficient in a power function production model can describe a measure of elasticity which is a percentage measure of the output response to a one percent change in input. This research was conducted to determine the response of milk production to input at the dairy farmer level. The research uses survey methods. A sample of 94 breeders was determined using the Multistage Random Sampling method. Research data was obtained through interviews with 4 groups of breeders. The analysis model used is multiple regression analysis and the F statistical test. The relationship between production and independent variables is modeled with the Cobb Douglas function. The research results show that the Cobb Douglas function equation model is . The F-test results show this model is significant (P<0.01) and reliable for explaining the influence between research variables. The coefficient of determination is 0.852, illustrating that the input variable has an effect of 85.2% on the amount of milk production. The two main inputs that have a significant effect are concentrate feed and cows with elasticity coefficients of 0.495 and 0.418 respectively. Dairy farming is in a constant state of returning to scale with a production elasticity value of 1 (one), this explains that every increase in all inputs proportionally, will increase the amount of milk production in the same proportion.